HUBUNGAN MOTIVASI BELAJAR TERHADAP PRESTASI SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Dandi Damara; Muhammad Rizal; Ratu Dinny Fauziah; Abdul Kodir; Yal Robiyansyah (Jurnal Cendekia Ihya, 2023)
This research is a type of quantitative research that uses a correlation approach. Data collection techniques use observation, questionnaire, and documentation methods. Questionnaires are used to obtain data about Learning Motivation (X), and student achievement results, namely report cards to obtain data about student achievement (Y). The sample in this study amounted to 53 samples using the probability sampling method and sampling calculations using the proportionate stratified random sampling technique. The aim of this research is to determine the relationship between learning motivation and learning achievement in Islamic Religious Education subjects at SMK Nurul Hidayah 1 Bogor. Based on the results of hypothesis testing with a significance value of 0.002 < 0.05, it can be concluded that the hypothesis in this research states that there is a relationship between learning motivation (X) and student achievement (Y) in Islamic Religious Education subjects at SMK Nurul Hidayah 1 Bogor. The magnitude of the influence can be seen in the Model Summary table, namely the R square value of 0.179 (17.9%). The magnitude of the relationship between learning motivation and student learning achievement is 0.423. The R value (0.423) is in the range 0.40 – 0.599 with a medium level of relationship. Therefore, the conclusions from this research can be stated as significant and there is a relationship between learning motivation (X) and student achievement (Y) in Islamic Religious Education subjects at SMK Nurul Hidayah 1 Bogor.